Optimalisasi Key Performance Indicators (KPI) Melalui Pendekatan Balance Scorecard Upaya Mengimplementasikan Performance Management System (PMS) Pada Perguruan Tinggi - Untung Rahardja; Muhamad Yusup Eva; Rosyifa Rosyifa (Universitas Raharja, 2012)
SQL Server Reporting Services is a way to analyze data, create reports using the indicators and gauges. Indicators are minimal gauges that convey the state of a single data value at a glance, and most are used to represent the state of Key Performance Indicators. Manage and harmonize the performance of an institution's educational institutions, especially universities with the performance of individuals or resources, no doubt is one of the essential elements for the success of an entity of the institution. Integrate the performance of an educational institution with individual performance is not an easy process, and therefore required a systematic approach to manage it. Implementation of a strategic management system based Balanced Scorecard can be used as a performance measurement system that will continuously monitor the successful implementation of the strategy of any public educational institution and measure the performance of its resources in a comprehensive and balanced, not the quantity but the emphasis is more concerned with the quality, so the performance of educational institutions at any time can be known clearly. Contribution of Key Performance Indicators to manage and harmonize the performance of any public institution is a solution in providing information to realize the extent of work that has set targets, identify and monitor measures of success, of course, with performance indicators show a clear, specific and measurable.